Deafness and Insight: On the Seductions of the Music/Language Analogy - Etherington, Ben (Paragraph (Modern Critical Theory Group), 2010)
This article contends that close attention to music/language analogies allows us to perceive how language attempts to gain an understanding of its own cognitive nature. The article does so by closely reading Paul de Man's 'The Rhetoric of Blindness', an essay in which de Man suggests that a detailed look at the analogies between musical and linguistic structures made by Jean-Jacques Rousseau in his Essay On the Origin of Languages helps reveal how literary criticism becomes 'blind' to its own metaphysical presuppositions. Scrutinizing the terms on which de Man engages Rousseau, the article argues that surface inconsistencies in de Man's use of musical concepts reveal a deeper pattern of 'deafness' which turns his notion of 'empty' subjectivity against itself. It concludes with some suggestions for how we might further develop the study of music/language analogies, a subject that has the potential to invigorate our understanding of the non-conceptual aspects of linguistic meaning.